Viability inhibition of A375 melanoma cells in vitro by a high-frequency nanosecond-pulsed magnetic field combined with targeted iron oxide nanoparticles via membrane magnetoporation. (2nd July 2021) - Mi, Yan; Dai, Lujian; Xu, Ning; Zheng, Wei; Ma, Chi; Chen, Wenjuan; Zhang, Qin
Abstract: Poor efficacy and low electrical safety are issues in the treatment of tumours with pulsed magnetic fields (PMFs). Based on the cumulative effect of high-frequency pulses and the enhanced perforation effect of targeted nanoparticles, this article proposes for the first time a new method that combines high-frequency nanosecond-pulsed magnetic fields (nsPMFs) with folic acid-superparamagnetic iron oxide nanoparticles (SPIONs-FA) to kill tumour cells. After determining the safe concentration of the targeted iron oxide nanoparticles, CCK-8 reagent was used to detect the changes in cell viability after utilising the combined method. After that, PI macromolecular dyes were used to stain the cells. Then, the state of the cell membrane was observed by scanning electron microscopy, and other methods were applied to study the cell membrane permeability changes after the combined treatment of the cells. It was finally confirmed that the high-frequency PMF can significantly reduce cell viability through the cumulative effect. In addition, the targeted iron oxide nanoparticles can reduce the magnetic field amplitude and the number of pulses required for the high-frequency PMF to kill tumour cells in vitro through magnetoporation. The objective of this research is to improve the electrical safety of the PMF with the use of nsPMFs for the safe, efficient and low-intensity treatment of tumours.